Improving Understanding of Fiqh Materials Through A Study of The Book of Fathul Qorib - Muhammad Fodhil; Muhammad Mashuri (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
Learning the Fathul Qorib book is one method of teaching fiqh subject. In order for the santri to comprehend, translate, draw a conclusion, contrast, explain, and deconstruct a dilemma pertaining to the material fiqh of worship and munakahat. This article is a case study using a qualitative methodology. Its findings show that reading the book Fathul Qorib can help people better grasp fiqh content. The lecture technique, in which instructional materials are delivered to students orally and with explanations in order to increase understanding, is used by fiqh professors. The Bandongan/Wetonan technique is a way of teaching that involves approaching pupils in a teacher-centered manner. A santri reads or interprets the text in front of his kyai using the Sorogan technique. The pupils will deliberate reading each other and correcting each other's readings. For both professors and students, practice, exercise, or demonstration are all acceptable.